Business strategy for market development in photography business for expose studio - Nauvall Rizal, Muhamad; Hamsal, Mohammad Hamsal (The Indonesian Journal of Business Administration, 2019)
Abstract – EXPOSÉ studio is a digital based commercial and advertising photography service located in Tebet, Jakarta Selatan. EXPOSÉ studio was named V-Studio back in 2013 when it was first established. At that time, the team consisted only with one lead photographer and a small number of freelancers followed numerous trends in photography industries, ranging from pre-wed, wedding, until modelling. EXPOSÉ studio changes its specialty from pre-wed or wedding photography into commercial and advertising photography. EXPOSÉ studio dedicates itself to not only providing creative business strategy consultation but also the execution itself. EXPOSÉ studio relies on business-to-business market segment that utilized its services for product catalogue and advertising purposes. Most of the clients came from fashion and food & beverages sectors within the level of SME. This situation has impacted EXPOSÉ studio sales performances which obstructs EXPOSÉ studio in generating revenues. Several analyses from external environment such as PESTEL and Porter’s Five Forces are conducted in order to gain information on whether the business is competitive enough in the industry. Apart from that, analysis from internal environment such as STP, Marketing Mix 7P, and VRIO are conducted in order to capture current state of EXPOSÉ studio from within. In formulating the strategy, author uses the means of interview and observation in order to gather insights before formulating the approaches. Porter’s Generic Strategy is used to decide in which direction will EXPOSÉ studio lean on in proceeding to its business core value. In order to elaborate the strategy formulation, author uses Diamond strategy, which encompass some aspects in strategy formulation such as arenas, vehicles, differentiators, staging, and economic logic, which become the guideline in executing the strategy. Finally, in order to capture the overview of strategy formulation and its implication to current business activities, author utilizes business model canvas. In implementing the strategy of market development, author summarizes into short-term and long-term planning which two of those planning will be constructed in the activity plan that will become guideline to execute business strategy of EXPOSÉ studio.  Keywords: Photography Business, Market Development, Diamond Strategy.